1982
DOI: 10.1159/000468579
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Phenomena: Results of a 10 Years’ (1970-1980) Literature Review

Abstract: A survey of the literature over 10 years (1970-1980) shows that the phenomenon of ‘rebound’ can appear after withdrawal of a large number of drugs belonging to various chemical classes and also, as a physiologic compensatory mechanism of the central nervous system, without drugs. Among the various drugs, benzodiazepine hypnotics are also mentioned in problems related to ‘rebound’ (insomnia, anxiety). Controversial opinions are expressed regarding the appearance of rebound insomnia or anxiety. It seems that tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Therefore, the occurrence of rebound is a function of the half-life of the drug effect relative to the rate at which the effects of the compensatory response dissipate. The appearance and severity of rebound phenomena depend greatly upon the speed with which the drug concentration drops following the termination of drug delivery (Lupolover et al, 1982). Given the development of acute tolerance on the pain threshold measure, a hyperalgesic rebound effect might be expected, especially considering the quick elimination of N 2 O.…”
Section: Acute Tolerance and Reboundmentioning
confidence: 99%
“…Therefore, the occurrence of rebound is a function of the half-life of the drug effect relative to the rate at which the effects of the compensatory response dissipate. The appearance and severity of rebound phenomena depend greatly upon the speed with which the drug concentration drops following the termination of drug delivery (Lupolover et al, 1982). Given the development of acute tolerance on the pain threshold measure, a hyperalgesic rebound effect might be expected, especially considering the quick elimination of N 2 O.…”
Section: Acute Tolerance and Reboundmentioning
confidence: 99%
“…Studies investigating drug rebound states have observed that the rebound which occurs following drug administration is typically opposite that o f the primary effect of the drug (Lupolover et al 1982). Since the PTZ discriminative stimulus is believed to be anxiogenic and the rebound following DZP adnfinistration generalizes to this cue, it is probable that the discriminative stimulus assodated with the primary effect of DZP is anxiolytic.…”
Section: Discussionmentioning
confidence: 99%
“…Rebound phenomena are not new in medicine, since they are produced by many nonpsychotropic medications such as clonidine, methyldopa, minoxidil, beta-blockers, vasopressors, diuretics and corticosteroids, to mention only a few (25). With prolonged drug usage, however, rebound phenomena may develop into more serious benzodiazepine withdrawal phenomena (10).…”
Section: Benzodiazepine Side-effectsmentioning
confidence: 99%